2017
DOI: 10.1016/j.ejso.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Is intraoperative touch imprint cytology indicated in the surgical treatment of early breast cancers?

Abstract: Introduction: Intraoperative touch imprint cytology (TIC) of the sentinel lymph node(s) (SLN(s)) in the treatment of breast cancer has significantly reduced the number of axillary block dissections (ABD) required during second surgeries. Based on recent studies, ABD was not considered necessary if the presence of tumor cells/micrometastasis was confirmed in the SLN(s) or in the case of macrometastases in a patient group meeting the inclusion criteria for the ACOSOG Z0011 study. Our aim was to determine the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
1
15
2
3
Order By: Relevance
“…However, recent studies have stated that TIC is not anymore, a useful technique to detect SLN metastasis in breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have stated that TIC is not anymore, a useful technique to detect SLN metastasis in breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, TIC specificity reached 100% in most of cases, whereas its sensitivity ranges between 69% to 99%. What lowers TIC sensitivity is the detection of micrometastases, which go unnoticed in 84% of cases [17]. This means that false positive results, leading to unnecessary axillary dissection, are quite uncommon, whereas false negative rates are extremely variable, involving mostly micrometastasis.…”
Section: Citationmentioning
confidence: 99%
“…In a retrospective analysis of 1,168 patients who underwent TIC, Horváth et al [8] reported a sensitivity of 57.18% and a specificity of 99.63% for this procedure. They indicated that TIC was less suited for the detection of metastases ≤2 mm, with 84.15% of micrometastases remaining undetected.…”
Section: Discussionmentioning
confidence: 99%
“…Nagashima et al [7] indicated that the specificity of TIC is high, but its sensitivity was low compared with FS. This low sensitivity could depend on its inability to identify micrometastases (≤2 mm) [8].…”
Section: Introductionmentioning
confidence: 99%
“…TIC lacks adequate sensitivity with micrometastasis and has a sensitivity of 70.3 per cent with macrometasiasis. 10 TIC would have been a cheap, simple and effective method to assess the SLN intraoperatively but unfortunately lacks the required sensitivity and specificity required to properly assess the axilla in early breast cancer and therefore cannot be used in intra-operative assessment of the SLN.…”
mentioning
confidence: 99%